Are tailored primary care services for social inclusion good value for money? A health economics evaluation with Monte-Carlo probabilistic sensitivity analysis comparing tailored social inclusion primary care services to mainstream primary care services for socially excluded people - Síle Kelly; Anne Dee; Patrick O’Donnell (International Journal for Equity in Health)
Abstract Background Socially excluded groups of people (SEP) live with resources so inadequate that it precludes them from participating fully in the normal acceptable living standards of society. They often have complex health and social care needs yet face structural and attitudinal barriers accessing mainstream healthcare. This can result in ambulatory-care sensitive conditions being left untreated in the community and contributes to the higher use of costly acute services in crisis mode by SEP. Tailored social inclusion primary care (SIPC) services can provide a flexible approach to engage with and meet the needs of this marginalised population. There is little evidence on the economic benefit of these services from the perspective of the publicly-funded health and social services. The aim of this study is to conduct an economic evaluation (cost-consequence analysis) of a single-centre SIPC clinic in the Mid-West region of Ireland over a 12-month period and to determine its value for money. The analysis compares cost outcomes between SEP who have access to a tailored SIPC service with those who do not. Methods A cost analysis of the part-time SIPC service, based on available Irish-sourced data on the usage and costs of acute care in the Health Service Executive (HSE), and a literature review were used to identify the cost and outcome parameters of the economic framework. A multi-variate probabilistic sensitivity analysis using Monte Carlo Simulation methodology was used to assess model uncertainty. Results The cost savings of investing in the part-time SIPC service providing care to 292 individuals, were estimated to be €718,890.90 with an estimated 658 bed days saved over a 12-month period. This represented a return of investment of €3.71 for every €1 spent. The sensitivity analysis supported the estimates with just a 2.2% likelihood of a negative return of investment. Conclusion This study found that investment in SIPC services, that can meet the needs of a marginalised population, represents good value for money from the perspective of the publicly funded health service. The findings are valuable in supporting stakeholders, policy-makers, and budget holders to make evidence-informed equitable decisions for optimal funding allocation within health and social services.